A comprehensive analysis of secondary flow effects on the performance of PEMFCs with modified serpentine flow fields. (15th January 2019) - Min, Chunhua; He, Jing; Wang, Kun; Xie, Liyao; Yang, Xuguang
Highlights: Modified serpentine flow fields were presented to improve PEMFC performance. Secondary flow is first used to explain performance improvement of PEMFC with modified serpentine flow fields. Secondary flow in the turn domain is very strong and the local current density is consequently increased. The oxygen concentration distribution uniformity is analyzed for modified serpentine flow fields. Abstract: Modified serially–linked serpentine flow fields are proposed for proton exchange membrane fuel cells (PEMFCs) and their performances are numerically studied. The effects of the segment number and the channel path number on the cell performance are analyzed. Especially The effect of the secondary flow on the cell performance is particularly discussed. Numerical results indicate that the modified serpentine flow fields can obviously improve the cell performance in comparison with the parallel flow field. The cell performances can be improved by increasing the segment number or the channel path number in each segment. The reactant transport under the rib and the secondary flow in the channel are considered as the main causes for the high cell performance of PEMFC with modified serpentine flow fields. The secondary flow can be generated by the combination of the under–rib flow and the serpentine turn. In comparison with the parallel flow field, the modified serpentine flow fields have higher average oxygen concentration but lower uniformity of the oxygen concentration distribution.